Efektivitas Terapi Multivitamin, Obat Cacing dan Premiks pada Sapi Terdiagnosa Hipofungsi Ovarium di Wilayah Kecamatan Prambanan, Yogyakarta - Niken Widarini; Imbang Ru Beda; Agustina Dwi Wijayanti (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2017)
Ovarian hypofunction in cattle is reproduction disorder related to massive economic loss. Etiology of this ovarium disfunction are low quality feed, minimum health concern, poor sanitation and pen problem. Eighty-five (85) Peranakan Ongole (PO), Peranakan Limosin (PL) and Peranakan Simental (PS) cows from Prambanan Sub District of Daerah Istimewa Yogyakarta were diagnosed with ovarian hypofunction by rectal palpation and physical examination. The cows were then programmed for ovary condition recovery by administration of vitamine A,D,E (IM), per oral anthelminthic bolus (Klosantel) and premix mixture in feed given daily for 4 weeks. After 4 weeks, the cows were re-examined. Sixty-two (72,9%) cows were recovered from ovary hypofunction, however ovaries of 23 (21,9%) cows were palpated abnormal, which require another administration of A,D,E (IM). There were no significant difference between the type of cows (PO,PL,PS) with recovery percentages after one programme therapy (P>0.05). It can be concluded that single injection of vitamin A,D, E , per oral bolus of Klosantel, and addition of premix into feed daily for 4 weeks were able to reduce 72,9% ovary hypofunction in Peranakan Ongole, Peranakan Limosin and Peranakan Simental cows at Prambanan sub district, Daerah Istimewa Yogyakarta.